The class analysis of households extended: Children, fathers, and family budgets - Stephen Resnick; Richard Wolff (University of Massachusetts, Department of Economics, 2007)
Since the 1994 publication of 'Bringing It All Back Home', commentators have raised a variety of questions and criticisms. Subsequently published applications of our books new class theory of households, by ourselves and others, have raised new issues not foreseen when we first developed the theory. In this paper we will address the major points of these reactions in ways that extend the class analysis of households well beyond our book and the literature it provoked and informed. The following topic areas will sequentially structure our presentation: children, interactions between the class structures of households and of enterprises, the class complexity of the household budget, class contradictions between households and enterprises, fathers household labor, and when children become household serfs. A short addendum addresses households from which class is absent because production there has dwindled and only consumption remains. Analyzing these new topics broadens and deepens two central points of our 1994 work. First, by conceiving class processes and contradictions and struggles over class as components of households, we can explore how class directly affects all the other, nonclass dimensions of those households: affective, marital, political, sexual, parental, financial, and so forth. We can show in particular how the class structure of households influences in contradictory ways (1) parents rearing of children, (2) household budgets, and (3) fathers household labor. Our analysis demonstrates and underscores how the good and bad of family life are intimately connected to class. Second, we will further develop or analysis of the interaction between household and enterprise class structures. Here we will stress how individuals are shaped by class processes, contradictions, and conflicts not only on the job but also and differently at home. Marxian analyses need to recognize this differential shaping to understand better the complexity of individual behavior including, as we will emphasize, its contradictory nature.
Keywords: 330